KELAYAKAN USAHATANI UBI KAYU DI DESA PETLENG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Padafing, Maria E.; Maure, Gerson Hans; Timung, Andri P. (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
Cassava plants are mostly cultivated to take advantage of the dry land conditions in Alor Regency. Cassava can be utilized and processed into various processed products. The research was carried out in Peteleng Village, Alor Tengah Utara District from March – May 2024. The sample size was 50 people using the Slovin formula. Data was collected through direct interviews with respondents from publication data from the Alor Regency Central Statistics Agency. The research aims to analyze the income and feasibility of cassava farming. The results of the research show that the income from cassava farming in Petleng Village is IDR. 2,571,374 with an R/C ˃ 1 value of 6.24 so that cassava farming is feasible.